A germanium and zinc chalcogenide as an anode for a high-capacity and long cycle life lithium battery. Issue 60 (30th October 2019) - Chen, Xu; Zhou, Jian; Li, Jiarui; Luo, Haiyan; Mei, Lin; Wang, Tao; Zhu, Jian; Zhang, Yong
Abstract : High-performance lithium ion batteries are ideal energy storage devices for both grid-scale and large-scale applications. Abstract : High-performance lithium ion batteries are ideal energy storage devices for both grid-scale and large-scale applications. Germanium, possessing a high theoretical capacity, is a promising anode material for lithium ion batteries, but still faces poor cyclability due to huge volume changes during the lithium alloying/dealloying process. Herein, we synthesized an amorphous germanium and zinc chalcogenide (GZC) with a hierarchically porous structure via a solvothermal reaction. As an anode material in a lithium ion battery, the GZC electrode exhibits a high reversible capacity of 747 mA h g −1 after 350 cycles at a current density of 100 mA g −1 and a stable capacity of 370 mA h g −1 after 500 cycles at a current density of 1000 mA g −1 along with 92% capacity retention. All of these outstanding electrochemical properties are attributed to the hierarchically porous structure of the electrode that has a large surface area, fast ion conductivity and superior structural stability, which buffers the volumetric variation during charge/discharge processes and also makes it easier for the electrolyte to soak in, affording more electrochemically active sites.